Transforming HR : The Digital Way (Trinity Journal of Management, IT & Media (TJMITM), 2016)
Digital Technology is radically changing the way how business  and governments operate in today’s scenario. From how  businesses and governments interact with customers, citizens  and suppliers, to how they manage their employees; digitization  has entered almost every aspect of our lives. The field of HR  is also one of the areas where digital technology has found its  way. Human resource management is now evolving into a more  technology-based profession. Gone are the days when HR  function shouldered the responsibility for managing people in  their old traditional ways. Transformation of HR through digital  technology has become call of the day. In the light of this rapidly  changing scenario where digitization is evolving at a breakneck  speed; HR departments that choose to ignore this transformation  could face obsolescence. This research paper talks about the  probable reasons why transformation in the field of HR is required  and what will be its impact on the business performance. This  is because many organizations may undertake this activity just  for the sake of it. It is quite possible that a transformation will  make a little impact on the organization. The paper also focuses  on the benefits and hindrances of digital technology in the area  HR and the future trends that can be seen in this field so that the  companies can make the best advantage of this transformation.
Keywords: Digitization; E-HR; Business Intelligence; HRIS; HR Transformation